Control of Crystallinity of Vinylene‐Linked Two‐Dimensional Conjugated Polymers by Rational Monomer Design. Issue 20 (11th March 2022) - Pastoetter, Dominik L.; Liu, Yannan; Addicoat, Matthew A.; Paasch, Silvia; Dianat, Arezoo; Bodesheim, David; Waentig, Albrecht L.; Xu, Shunqi; Borrelli, Mino; Croy, Alexander; Richter, Marcus; Brunner, Eike; et al.
Abstract: The interest in two‐dimensional conjugated polymers (2D CPs) has increased significantly in recent years. In particular, vinylene‐linked 2D CPs with fully in‐plane sp 2 ‐carbon‐conjugated structures, high thermal and chemical stability, have become the focus of attention. Although the Horner‐Wadsworth‐Emmons (HWE) reaction has been recently demonstrated in synthesizing vinylene‐linked 2D CPs, it remains largely unexplored due to the challenge in synthesis. In this work, we reveal the control of crystallinity of 2D CPs during the solvothermal synthesis of 2D‐poly(phenylene‐quinoxaline‐vinylene)s (2D‐PPQVs) and 2D‐poly(phenylene‐vinylene)s through the HWE polycondensation. The employment of fluorinated phosphonates and rigid aldehyde building blocks is demonstrated as crucial factors in enhancing the crystallinity of the obtained 2D CPs. Density functional theory (DFT) calculations reveal the critical role of the fluorinated phosphonate in enhancing the reversibility of the (semi)reversible C−C single bond formation. Abstract : We reveal the control of crystallinity during the solvothermal synthesis of 2D‐poly(phenylenequinoxalinevinylene)s (2D‐PPQVs) and 2D‐poly(phenylene‐vinylene)s (2D‐PPVs) through the Horner‐Wadsworth‐Emmons (HWE) polycondensation by the employment of fluorinated phosphonates and rigid aldehyde building blocks.